Community Structure Of Seagrass In Southeast Waters Cempedak Island West Kalimantan - Safitri, Ikha; Sofiana, Mega Sari Juane; Yudhoyono, Billget Mansirit; Kusumardana, Setra (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2024)
Cempedak Island is one of the Coastal and Small Islands Conservation Areas (KKP3K) in West Kalimantan has various marine biological resources and important ecosystems, including seagrass. Seagrass is used as the main food source for dugong, potential habitat for various types of organisms, and potential to be developed as marine ecotourism. On the other hand, seagrass ecosystems faced threats, such as high sedimentation and the influence of anthropogenic activities. It is unknown about the current status of seagrass on Cempedak Island. This research aimed to analyze the structure of seagrass in the southeastern waters of Cempedak Island. Seagrass data collection was carried out in the tidal zone using line transect of 70 m and a quadratic transect of 1x1 m2. Data collection on seagrass and water parameters was carried out in October 2023. Determination of research sites was done using an explorative method based on the presence of seagrass. The seagrass found consisted of 4 species, namely Enhalus acoroides, Cymodocea rotundata, Halodule pinifolia, and Halophila ovalis. Seagrass cover ranged from 9.17–16.74%, with an abundance of 1.4–373.3 ind/m2. The diversity index (H') is in the low to medium category, the uniformity index (E) is in the medium category and the dominance index (C) is in the low category. Conditions of water quality parameters were into the optimal range to support seagrass life.